Catalytic activities of Ag/C decorated with small amounts of Au and Pt for glycerol oxidation. (6th November 2020) - Wu, Jialu; Cai, Nan; Dong, Rulin; Jin, Changchun
Abstract: The two-step decoration of the Ag nanoparticles supported on carbon black (Ag/C) with Au and Pt, the electrooxidation of glycerol on the Pt/Au/Ag/C catalysts in alkaline solution, and the effect of the amounts of Au and Pt on the catalytic activity of Pt/Au/Ag/C are investigated. The decoration of Ag/C is performed by electrochemically depositing a small amount of Au and then Pt on Ag/C, and the Ptx /Auy /Ag100 /C catalysts with different x : y :100 ratios (0.15 ≤  x  ≤ 1.9 and 0.2 ≤  y  ≤ 1.5) are obtained. Physical and electrochemical characterizations reveal that small parts of the Ag surfaces are covered by the deposited Au and Pt. Ptx /Auy /Ag100 /C mainly shows Pt-relevant behaviors in glycerol oxidation, and Pt1.3 /Auy /Ag100 /C exhibits high catalytic activities. The results reveal that the surface decoration is a useful method of fabricating efficient ternary catalysts at low cost. Highlights: Pt/Au/Ag/C is prepared by decorating Ag/C with small amounts of Au and Pt. Activity of Pt/Au/Ag/C depends on the decoration sequence and masses of Au and Pt. Pt1.3 /Auy /Ag100 /C (y ≤ 1.5) shows high catalytic activity for glycerol oxidation.